Connexin 43 hemichannels and intracellular signaling in bone cells - Plotkin, Lilian I. (Frontiers in Physiology, 2014)
Cell function and survival are controlled by intracellular signals, and modulated by surrounding cells and the extracellular environment. Connexin channels participate in these processes by mediating cell-to-cell communication. In bone cells, gap junction channels were detected in the early 1970s, and are present among bone resorbing osteoclasts, bone forming osteoblasts, and osteocytes - mature osteoblasts embedded in the mineralized matrix. These channels are composed mainly by Cx43, although the expression of other connexins (45, 46 and 37) has also been reported. It is now believed that undocked Cx43 hemichannels (connexons) formed in unopposed cell membranes facing the extracellular environment participate in the interaction of bone cells with the extracellular environment, and in their communication with neighboring cells. Thus, we and others demonstrated the presence of active hemichannels in osteoblastic and osteocytic cells. These hemichannels open in response to pharmacological and mechanical stimulation. In particular, preservation of the viability of osteoblasts and osteocytes by the anti-osteoporotic drugs bisphosphonates depends on Cx43 expression in vitro and in vivo, and is mediated by undocked hemichannels. Cx43 hemichannels are also required for the release of prostaglandins and ATP by osteocytes, and for cell survival induced by mechanical stimulation in vitro. Moreover, they are required for the anti-apoptotic effect of parathyroid hormone in osteoblastic cells. This review summarizes the current knowledge on the presence and function of undocked connexons, and the role of hemichannel regulation for the maintenance of bone cell viability and, potentially, bone health.